2016
DOI: 10.3109/02770903.2016.1140181
|View full text |Cite
|
Sign up to set email alerts
|

Association between asthma and dysphonia: A population-based study

Abstract: Asthma patients are predisposed to subjective dysphonia due to demographic and clinical characteristics (older age, female, and higher stress level) as well as to asthma itself. However, asthma was not associated with organic laryngeal lesions in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
2
5
0
Order By: Relevance
“…Laryngeal mucosal inflammation was reported in only three asthmatic patients, and no laryngeal candidiasis was found. Our results were close to those found by Park et al, 13 who performed a large cross-sectional study comparing subjective voice complaints and organic laryngeal diseases (vocal cord polyps, vocal cord nodules, or laryngitis).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Laryngeal mucosal inflammation was reported in only three asthmatic patients, and no laryngeal candidiasis was found. Our results were close to those found by Park et al, 13 who performed a large cross-sectional study comparing subjective voice complaints and organic laryngeal diseases (vocal cord polyps, vocal cord nodules, or laryngitis).…”
Section: Discussionsupporting
confidence: 92%
“…10,12 Dysphonia has been described as more frequent in asthma than healthy subjects (11.3% vs. 5.5%). 13 An uncontrolled study on asthma has estimated an association with dysphonia in 50% of cases. 14 The main hypothesis, supported by only two limited uncontrolled studies, 15,16 was that dysphonia was caused by inhaled corticosteroids by favoring candidiasis or inducing myopathic bowing of the vocal cords.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study showed that children with asthma had higher scores on pVHI compared to healthy children, indicating a greater likelihood of the development of voice complaints. These results are similar to the findings of two studies with adult studies where the participants with asthma scored significantly higher on voice quality parameters than the control group [16,17]. In addition, patients with allergy have also been reported to have a higher degree of vocal dysfunction measured with VHI than patients without allergy [18].…”
Section: Discussionsupporting
confidence: 88%
“…In addition, we showed that pVHI scores were correlated positively with AR severity [19]. Previous studies with adult participants have shown that dysphonia was significantly more prevalent in patients with asthma compared to healthy participitans [5,16,17]. Restricted expiration, decreased lung volume, diaphragm, together with fluctuations in intra-thoracic and intra-abdominal pressures might hypothetically explain the significantly higher prevalence of voice disorders in patients with asthma.…”
Section: Discussionmentioning
confidence: 51%